Development of hplc analysis for detection of lycopene in tomato and crude palm oil - Azizan, Abdul Aziz (2006)
In this study the effect of type and ratio of solvents liquid-liquid extraction from Tomato is considered in this research. Then the method will be done to the Crude Palm Oil (CPO). Extraction is a process to obtaining something from mixture or compound by chemical or physical methods. Liquid-liquid extraction is used to extract and purify carotenoids from CPO and then this sample will be analysis in High Performance Liquid Chromatographer (HPLC). Natural antioxidants occur in carotenoids are lycopene, α-carotene and β-carotene. Natural antioxidants can be founds in almost all plant, microorganism, fungi and animal tissue. Lycopene is antioxidant that uses to avoid some kind of cancer like prostate cancer. Lycopene is mainly found in the red fruid like tomato and watermelon. This is because lycopene is the red pigment that responsible to the red colour of the fruits. Nowadays, major source of lycone are from tomato although the high content of lycopene are found in watermelon.